LAZISMU KENDAL: Problem Analysis and Fundraising Strategy - Baharudin Baharudin; Nurudin Nurudin; Faisal Amarsah (AKSES: Jurnal Ekonomi dan Bisnis, 2023)
The results of the pre-research show that the collection of zakat, infaq and shodaqoh Lazismu Kendal funds has experienced several problems. Among them, minimal regional employees and not knowing the location of Lazismu Kendal. Researchers used a qualitative method with descriptive analysis. The results of the study explained that Lazismu Kendal has two fundraising strategies, namely direct fundraising and indirect fundraising. The results of the strategy that has been implemented can be effective. This is according to data on zakat funds for 2016-2019 which has experienced a significant increase